Implementasi Aplikasi Sistem Keuangan Desa (Siskeudes) Di Kantor Desa Moncobalang Kecamatan Barombong Kabupaten Gowa - Amelia, Renita; Malik, Ihyani; Rahim, Samsir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to explain the implementation of the Village Financial System Application at the Moncobalang Village Office, Barombong District, Gowa Regency. This study qualitative research with data collection techniques used interview, observation and literature study. The data was analyzed interactively which took place continuously until the data saturated. The results shower that in the implementation of the village financial system, in terms of policy content and policy environment, it had been implemented properly, but there were still some obstacles that occured, such as a lack of adequate human resources (HR) so that the financial management process was not optimal. In order for the implementation of the siskeudes had run well, the government had to hold regular training and guidance for the siskeudes.Keywords: Implementation of Siskeudes, Village Financial Management.